Colombia : a country study - Hudson, Rex A. (Area handbook series., 2010)
This series deal with a particular foreign country, describing and analyzing its political, economic, social, and national security systems and institutions, and examining the interrelationships of those systems and the ways they are shaped by historical and cultural factors.